The Impact of Pediatric Opioid-Related Visits on U.S. Emergency Departments - Tiffany Champagne-Langabeer; Marylou Cardenas-Turanzas; Irma T. Ugalde; Christine Bakos-Block; Angela L. Stotts; Lisa Cleveland; Steven Shoptaw; James R. Langabeer (MDPI AG, 2022)
Background: While there is significant research exploring adults' use of opioids, there has been minimal focus on the opioid impact within emergency departments for the pediatric population. Methods: We examined data from the Agency for Healthcare Research, the National Emergency Department Sample (NEDS), and death data from the Centers for Disease Control and Prevention. Sociodemographic and financial variables were analyzed for encounters during 2014-2017 for patients under age 18, matching diagnoses codes for opioid-related overdose or opioid use disorder. Results: During this period, 59,658 children presented to an ED for any diagnoses involving opioids. The majority (68.5%) of visits were related to overdoses (poisoning), with a mean age of 11.3 years and a majority female (53%). There was a curvilinear relationship between age and encounters, with teens representing the majority of visits, followed by infants. The highest volume was seen in the Southern U.S., with over 58% more opioid visits than the next highest region (Midwest). Charges exceeded USD 157 million, representing 2% of total ED costs, with Medicaid responsible for 54% of the total. Conclusions: With increases in substance use among children, there is a growing need for pediatric emergency physicians to recognize, refer, and initiate treatments.